2010
DOI: 10.1159/000287953
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Concentrations of Functionally Important Amino Acids and Metabolic Compounds in Patients with Mild Cognitive Impairment and Alzheimer’s Disease

Abstract: Cerebrospinal fluid (CSF) biomarkers play an important role in the differential diagnosis of neurodegenerative diseases such as Alzheimer’s disease (AD) and its postulated precursor stage mild cognitive impairment (MCI). While CSF tau protein, phospho-tau protein and β-amyloid have become part of the diagnostic process in clinical routine, the importance of several other biomarkers remains quite unclear. Among these, amino acids and metabolic compounds have been studied in clinical conditions mostly other than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 83 publications
2
32
0
Order By: Relevance
“…This effect can lead to glutamate dyshomeostasis and/or glutamate excitotoxicity. This phenomenon has been suggested in AD because AD patients have increasing glutamate levels in their cerebral spinal fluid as dementia progresses (Jimenez-Jimenez et al, 1998;Kaiser et al, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…This effect can lead to glutamate dyshomeostasis and/or glutamate excitotoxicity. This phenomenon has been suggested in AD because AD patients have increasing glutamate levels in their cerebral spinal fluid as dementia progresses (Jimenez-Jimenez et al, 1998;Kaiser et al, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…Notably, two analyses have reported alterations in CSF metabolome of AD. One study has showed the increase of the concentrations of eight amino acids in AD versus MCI [111]. Another larger examination, after measuring 343 analytes has also led to detect eight molecules with statistical significance; interestingly, one of these markers, cortisol, correlated with the advancement of the disease [112].…”
Section: Upcoming Candidate Biomarkersmentioning
confidence: 99%
“…As progressive failure of neuronal networks and neurotransmitter systems is one of the prominent features of AD, it is not surprising that in the CSF of AD patients abnormal concentrations of neurotransmitters and their metabolites have been found. Hence, many studies tried to assess the diagnostic potential of CSF neurotransmitters (110,111). However, the results on CSF monoamine metabolites in AD patients are conflicting (112,113).…”
Section: Novel Csf Biomarkersmentioning
confidence: 99%